Niger : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Third Review Under the Extended Credit Facility (ECF) for Niger. Program implementation to date is satisfactory and all quantitative performance criteria at end-June 2009 were met. The revenue performance is strong and domestic arrears repayment higher than anticipated. All indicative targets at end-September were observed, confirming these trends. On the structural front, the authorities have implemented measures to strengthen debt management, improve budget monitoring, and enhance the business environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet